Introduction. (July 2019) - Fazio, Giorgio; Ferrara, Alessandro
The contributions grouped in this special section on 'Realizing social freedom: a conversation on Honneth's idea of socialism' critically engage Honneth's latest philosophical production and address Freedom's Right and The Idea of Socialism from a cross-cutting perspective. The contributions grouped in the first round of discussion revolve around the problems raised by the theory of justice outlined in Freedom's Right, though they also address the subsequent developments undergone by this theory in the book on socialism. The contributions grouped in the second round of discussion, instead, concentrate on Honneth's proposal for a renewal of our understanding of socialism, with the aim of assessing its continuity and discontinuity in relation to the systematic retrieval of Hegel's Philosophy of Right undertaken in Honneth's earlier book.